Developmental Integration of Endosymbionts in Insects - Rafiqi, Ab. Matteen; Polo, Priscila G.; Milat, Nihan Sultan; Durmuş, Zelal Özgür; Çolak-Al, Birgül; Alarcón, Mauricio E.; Çağıl, Fatma Zehra; Rajakumar, Arjuna (Frontiers in Ecology and Evolution, 2022)
In endosymbiosis, two independently existing entities are inextricably intertwined such that they behave as a single unit. For multicellular hosts, the endosymbiont must be integrated within the host developmental genetic network to maintain the relationship. Developmental integration requires innovations in cell type, gene function, gene regulation, and metabolism. These innovations are contingent upon the existing ecological interactions and may evolve mutual interdependence. Recent studies have taken significant steps towards characterizing the proximate mechanisms underlying interdependence. However, the study of developmental integration is only in its early stages of investigation. Here, we review the literature on mutualistic endosymbiosis to explore how unicellular endosymbionts developmentally integrate into their multicellular hosts with emphasis on insects as a model. Exploration of this process will help gain a more complete understanding of endosymbiosis. This will pave the way for a better understanding of the endosymbiotic theory of evolution in the future.